KEMUNGKINAN PENGEMBANGAN TERNAK PADA DAERAH LAHAN KRITIS DI KABUPATEN BANYUMAS THE POSIBILITY OF LIVESTOCK DEVELOPMENT ON CRITICAL LAND IN BANYUMAS REGENCY - Suwandyastuti, S.N.O. (Pembangunan Pedesaan, 2010)
The land as the ecological base of the farming system is one of the important factors for the farmers. The wrong management of the soil may cause the critical farming land. An experiment had been conducted to study the possibility of livestock development which also could improve the soil fertility in the critical land. Survey method was used in this research on the critical land decided by the Board Government of Banyumas Regency, namely, Ajibarang, Pekuncen, Gumelar, Wangon, and Lumbir Districs. The sample of villages was determined from the five districts, i.e., 50% of total villages of each district). Determination of villages were made by a Stratified Random Sampling on the basic of evaluation result both from the stand point of natural physic and from the standpoint of socio-economic. Data were collected directly and by interview supported with the previously prepared questionnaires. The result showed that all of the critical lands from five districts in Banyumas Regency were still capable to receive the livestock and could be utilized as the land of sheep and goat. The average PMH was 1291,51 ST and PMK (except Ajibarang) was 326,61 ST, although the TDN (3,1 kg/kg BK) and CP (8,8% DM) were low. It could be concluded from this research that the critical land area in Banyumas Regency was capable to make sheep and goat livestock development because the area condition was open with the area opening index of 3.366.